Antología del pensamiento de lengua española en la edad contemporánea - Gaos, José (1982)
Contiene escritos de: Justo Sierra, Marcelino Menéndez y Pelayo, Carlos Arturo Torres, Miguel de Unamuno, Francisco Giner de los Ríos, José Ingenieros, Alejandro O. Deustua, Alejandro Korn, José Ortega y Gasset, José Vasconcelos, Carlos Vaz Ferreira, Antonio Caso, Francisco Romero, Alfonso Reyes.